Priority Analysis of Robusta Coffee (Coffea canephora) Harvesting Facilities to Reduce Quantity Loss Using the AHP (Analytical Hierarchy Process) Method: Priority Analysis of Robusta Coffee (Coffea canephora) Harvesting Facilities to Reduce Quantity Loss Using the AHP (Analytical Hierarchy Process) Method - Maharani, Ni Putu Dewi Pradnya; Aviantara, I Gusti Ngurah Apriadi; Wirawan, I Putu Surya (Jurnal BETA (Biosistem dan Teknik Pertanian), 2024)
Coffee is a plantation product that serves as a major source of foreign exchange for the country. Robusta coffee is a production base in several regions in Indonesia, including Bali, where the largest production occurs in Pupuan District, Tabanan Regency. Despite the high production volume, Robusta coffee in Pupuan District is still mostly processed using traditional equipment, maintained due to the high investment cost of modern post-harvest facilities. This study aims to determine the appropriate criteria and sub-criteria for prioritizing robusta coffee postharvest facilities and to identify the priority facilities that can reduce quantity losses. The study uses a purposive sampling method to select potential respondents and employs the Analytical Hierarchy Process (AHP) for analysis. The results indicate that the huller is the priority tool in postharvest handling of Robusta coffee and can effectively reduce quantity loss.